KESTABILAN ZAT WARNA ALAMI DARI UMBI KETELA UNGU (Ipomoea batatas) - Ibnu Khaldun (FKIP USK, 2013)
Researcher has conducted a study on the stability of natural pigments which is derived from sweet potato (Ipomea batatas). The aim of this study was to determine the stability of natural pigments from sweet potato of the variation of heating temperature, long warm-up, long storage and long exposure to sunlight. The populations of this study those fresh sweet potatoes ibaraki varieties as much as 2 kg. The samples used in this study were 100 grams of sweet potatos that have been peeled and grated, then be extracted with 20 mL of distilled water at a temperature of 50 0C and blended so that it became a slurry and then squeezed, then do the identification of anthocyanin compounds in the sample. The extract of sweet potato at pH 6 measured the wavelength of maximum, then anthocyanin concentration was calculated using the pH-differential method. Further, it was tested the stability of the dye to the variation of heating temperature, long warm-up, long storage and long exposure to sunlight at a wavelength of maximum. The results showed that at pH 6 sweet potatos have a wavelength of 536 nm and concentraining anthocyanin with 10,02 mgL-1 of concentrations. Stability of the dye from sweet potatos extracts to heating temperature variation decreased absorbance values by an average of 0,004, a decreased of the heating value of the average absorbance of 0,008 and of storage duration decreased the absorbance values by an average of 0,007. Whereas long exposure to sunlight absorbance values increased by an average of 0,009. The conclution of the researche is the intensity of sweet potatoes extract color was reduced to the variation of heating temperature, heating time and saving time. The intensity of yam’s extract color increased to along exposure of sunlight.